Factors influencing the decision of South Korean families to send their children to international schools in Phuket - Ratchasom, Nattatinna; Saenphithak, Punchida (Journal of International Studies, Prince of Songkla University, 2026)
This study aims to analyze the factors influencing the decision-making process of South Korean families in sending their children to study at international schools in Phuket Province. The research employs a qualitative research methodology using a case study approach to gain an in-depth understanding of parents’ experiences, perspectives, and perceptions within the social and educational context. The participants were selected through purposive sampling and consisted of four South Korean families whose children had been enrolled in international schools in Phuket for at least one year. The findings reveal that the decision-making factors can be explained through Maslow’s Hierarchy of Needs. Parents placed significant emphasis on social safety and a secure learning environment, corresponding to safety needs, along with the quality of curricula and educational standards. Furthermore, the development of English language proficiency and preparation for higher education in an international context reflect higher-level needs, including esteem and self-actualization. These findings indicate that choosing an international school represents a strategic decision-making process that integrates multiple levels of human needs in a systematic manner.